Index Card Match Model in Primary School: Effects on Learning and Civic Attitudes - Mufarizuddin, Mufarizuddin; Rizal, Muhammad Syahrul; Daulay, Musnar Indra (Universitas PGRI Yogyakarta, 2025)
Civic education at the primary level in Indonesia often lacks effectiveness due to conventional instructional methods that fail to engage students meaningfully or foster participatory civic dispositions. The existing literature rarely explores integrative learning models that simultaneously address cognitive understanding and civic attitudes within a single framework. This quasi-experimental study investigates the effect of the Index Card Match (ICM) model on the learning outcomes and civic attitudes of fifth-grade students in civic education. Sixty students from Pekanbaru were divided into experimental and control groups, with pre- and post-tests administered. Data were analyzed using independent t-tests, showing statistically significant improvements in the experimental group for learning outcomes (p = 0.001) and civic attitudes (p = 0.003). The effect sizes were moderate to large, indicating statistical significance and meaningful pedagogical impact. The strength of this study lies in its integrated evaluation of cognitive and affective domains, demonstrating how structured collaborative activities foster deeper conceptual understanding and internalization of civic values such as responsibility, tolerance, and cooperation. These findings offer actionable insights for curriculum developers and teachers to adopt interactive learning models that reinforce academic content and character formation within the elementary civic education context. Keywords: Index Card Match, civic attitudes, civic education, collaborative learning